Software engineering - Schach, Stephen R.; Schach, Stephen R. (Unites States of America : Aksen Associates, Inc., 1990)
The aim of software engineering is he production of quality software, software that is delivered on time and within budget, and that satisfies all its requirements. To this end, a variety of techniques have been developed for performing the various software production tasks, from requirements and specifications to maintenance. An inportant aspect of software engineering is that software production should be well supported by a set of appropriate automated tools.
Part one. Introduction to software engineering -- Chapter 1. Scope of software engineering -- Chapter 2. Software production and its difficulties -- Part two Software life cycle -- Chapter 3. Software life-cycle models -- Chapter 4. Software planning -- Chapter 5. Stepwise refinement : a basic software engineering technique -- Chapter 6. Testing -- Part three Specification methods -- Chapter 8. Modularity : and beyond -- Chpater 9. Design methods -- Chapter 10. Implementation -- Chapter 11. Maintenance -- Part four Major topics in software engineering -- Chapter 12. CASE (Computer-aided software enginnering) -- Chapter 13. Portability and reusability -- Chapter 14. Ada and software engineering -- Chapter 15. Experimentation in software engineering -- Chapter 16. Automatic programming
Includes bibliographical references and index.
Keywords: SOFTWARE ENGINEERING